King Arthur - Hardy-Gould, Janet; Rator, Axel (Oxford ; New York ; Oxford University Press, 2008)
Retells, in simplified language and graphic novel format, the legend of King Arthur.
Young Adult
Young Adult
Keywords: Arthur, King -- Legends -- Comic books, strips, etc; Arthur, King -- Legends -- Comic books, strips, etc; English language -- Textbooks for foreign speakers; Folklore -- England; Readers (Adult); Reading comprehension -- Problems, exercises, etc; Comic books, strips, etc; English as a second language; Folklore -- England; Reading comprehension -- Problems, exercises, etc; Reading materials; Great Britain -- History -- Anglo-Saxon period, 449-1066 -- Comic books, strips, etc; Great Britain -- History -- 0-1066 -- Comic books, strips, etc